Home and identity in late life: international perspectives - Rowles, Graham D.; Chaudhury, Habib (Springer, 2005)
"Presenting insightful essays and findings from empirical studies, leading contemporary scholars examine the meaning of home to elders and the ways in which this meaning may be sustained, threatened, or modified in association with both normal and pathological changes with growing old. For example, health and well being can be affected by an environmental change, such as a change in an established neighborhood or a forced relocation. Section topics explored include: The Essence of Home; Disruptions of Home: Creating and Recreating Home; and Community Perspective on the Meaning of Home. The volume concludes with a series of critical commentaries that add unique perspectives on the topic"-Provided by the Publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Kulturvergleich; Zuhause; Soziale Identität; Alter